Functional Characterization of Pembrolizumab Produced in Nicotiana benthamiana Using a Rapid Transient Expression System - Phakham, Tanapati; Bulaon, Christine Joy I.; Khorattanakulchai, Narach; Shanmugaraj, Balamurugan; Buranapraditkun, Supranee; Boonkrai, Chatikorn; Sooksai, Sarintip; Hirankarn, Nattiya; Abe, Yoshito; Strasser, Richard; Rattanapisit, Kaewta; Phoolcharoen, Waranyoo (Frontiers in Plant Science, 2021)
The striking innovation and clinical success of immune checkpoint inhibitors (ICIs) have undoubtedly contributed to a breakthrough in cancer immunotherapy. Generally, ICIs produced in mammalian cells requires high investment, production costs, and time consuming. Recently, plants are considered as an emerging protein production platform due to its cost-effectiveness and rapidity for the production of recombinant biopharmaceuticals. This study explored the potential of plant-based system to produce an anti-human PD-1 monoclonal antibody (mAb), Pembrolizumab, in Nicotiana benthamiana. The transient expression of this mAb in wild-type N. benthamiana accumulated up to 344.12 ± 98.23 µg/g fresh leaf weight after four days of agroinfiltration. The physicochemical and functional characteristics of plant-produced Pembrolizumab were compared to mammalian cell-produced commercial Pembrolizumab (Keytruda®). SDS-PAGE and western blot analysis results demonstrated that the plant-produced Pembrolizumab has the expected molecular weight and is comparable with the Keytruda®. Structural characterization also confirmed that both antibodies have no protein aggregation and similar secondary and tertiary structures. Furthermore, the plant-produced Pembrolizumab displayed no differences in its binding efficacy to PD-1 protein and inhibitory activity between PD-1 and PD-L1 interaction with the Keytruda®. In vitro efficacy for T cell activation demonstrated that the plant-produced Pembrolizumab could induce IL-2 and IFN-γ production. Hence, this proof-of-concept study showed that the plant-production platform can be utilized for the rapid production of functional mAbs for immunotherapy.